Islam Rasional (Gagasan dan Pemikiran Prof. Dr. Harun Nasution) - Alef Theria Wasim (Al-Jami'ah Research Centre, 1996)
Islam Rasional serves a dual function. It is intended in the first place as a textbook for students of Islamic studies, especially those who wish to examine in a more sustained way than is usually the case how theology and religious studies are related to each other. Islam Rasional playing out two roles. 1) as a thought rationally looking at Islam and 2) as a thought rationally looking at al-Qur’an as a religious source which does not consist of everything and this is only accepted rationally. It is playing out both that some scholars would obviously like to see as quite disjunct and which others would see as indistinguishable one. This seems to create criticism. Islamic and rational thought can be engaged in a dialectical interaction which enhances the validity and authenticity of each and Islam Rasional allows these disciplines to bed down together or to be integrated combined this does not mean that offspring which might result from such of union will necessarily be a new integral theological science of religion though this is perhaps what a growing number of scholars seem to envisage, and if such is a felt necessity there is no point in the champions of methodological rigout on either side of the marital bed saying this must not be. Its position is that while it has to move beyond either polarized antagonism or tolerant coexistence, the rigorously desired mutual dependence will in fact more fully authenticate the distinctiveness of the two approaches. But in view of the intrinsic independence, to delineate any precise methodological autonomy for each will for great subtlety, or the distinctiveness will be overstated and oversimplified. The understanding of either approach, and certainly of their interrelation, must hinge largely on our analysis and interpretation of the intrinsic character of religion. And here Islam Rasional has to affirm the incongruity of setting ‘faith’ against ‘religion’, even if in all religions there are core points of experience that seem to transcend the religion. In particular, it is in the dialectical interdependence, that relation between the theology, the diverse forms in religion, and the religious studies process in further interaction with contextual life that provides the key for understanding how to relate theology to religion and thus to religious studies (Islamic Studies). Islam Rasional consists of basic and primary grinding of Islamicisty, a specifically religious one, which means that it should welcome any potentially instructive insight into the richly varied dimensions of religious life. The inner structuring of Islam, which could relate the existence of for example sciences in Islam. In the history of Islam, Prof. Dr. Harun Nasution observes, the conflicts are not between science and religion, but among more or less, the schools (madhhab) of Islamic theology, and Islamic law. A science of religion, even if concerned primarily in such particularity. Inclusiveness possible to many theologies, the inclusiveness which is hopefully increasingly realized in further inter-religious exchange, it seems to be a rather different order. Theology and religion (Rationality and Islam or reason and revelation, or al-‘aql and al-waḥy) must be recognized as thoroughly independent, but their distinctive procedures cannot be over liked.